Cover Feature: Self‐Aggregation‐Controlled Rapid Chemical Bath Deposition of SnO2 Layers and Stable Dark Depolarization Process for Highly Efficient Planar Perovskite Solar Cells (ChemSusChem 16/2020). Issue 16 (27th July 2020) - Ko, Yohan; Kim, Youbin; Lee, Chanyong; Kim, Taemin; Kim, Seungkyu; Yun, Yong Ju; Gwon, Hui‐jeong; Lee, Nam‐Ho; Jun, Yongseok
Abstract : The Cover Feature shows highly efficient perovskite solar cells with tin oxide layers by self‐aggregation controlled rapid chemical bath deposition. More information can be found in the Full Paper by Y. Ko, Y. Kim, et al .